Diagnostic accuracy of [99mTc]pertechnetate scintigraphy in pediatric patients with suspected Meckel’s diverticulum: a 12-year, monocentric, retrospective experience - Li, Bo; Gao, Jian; Ding, Xintao; Li, Xiali; Yu, Yue; Long, Ye; Wang, Xiaohui; Wu, Xinyu; Gao, Yongju (Frontiers in Medicine, 2025)
ObjectiveTo assess the diagnostic accuracy of [99mTc]pertechnetate scintigraphy in pediatric patients with suspected Meckel’s diverticulum (MD).MethodsA retrospective study was conducted on 94 pediatric patients who presented with symptoms suggestive of MD and underwent [99mTc]pertechnetate scintigraphy at Henan Provincial People’s Hospital between September 2012 and August 2024. For patients with high clinical suspicion and equivocal scintigraphy results, Single Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) or repeat scintigraphy was conducted. Hemoglobin levels were measured in all patients, and their correlation with MD was analyzed. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated by comparing scintigraphic results with surgical and histopathological findings.ResultsAmong the 94 patients, 20 (21.3%) had positive [99mTc]pertechnetate scintigraphy, all confirmed as true positives through laparoscopic resection and histopathological examination. Of the 74 patients with negative scintigraphy results, 6 were found to be false negatives based on surgical findings, and 68 were confirmed as true negatives. Therefore, the sensitivity, specificity, PPV, and NPV were 76.9% (20/26), 100.0% (68/68), 100.0% (20/20), and 91.9% (68/74), respectively. The overall diagnostic accuracy was 93.6% (88/94). SPECT/CT was utilized in three cases, enhancing diagnostic precision in patients with equivocal planar imaging results. Repeat scintigraphy was performed in three patients with high clinical suspicion and negative initial scans, resulting in one additional positive diagnosis. MD patients exhibited significantly lower hemoglobin levels compared to non-MD patients (88.69 ± 20.39 g/L vs. 107.24 ± 29.28 g/L; p = 0.0009), with hemoglobin showing moderate predictive value (AUC = 0.70; 95% CI: 0.60–0.81).Conclusion[99mTc]pertechnetate scintigraphy is a highly specific and accurate tool for diagnosing MD in pediatric patients. However, due to the potential for false negatives, additional SPECT/CT imaging or repeat scintigraphy may be warranted in cases with high clinical suspicion.